ANALISIS DIAGNOSTIK KESULITAN BELAJAR MAHASISWA PADA MATA KULIAH MODEL LINIER - Malim Muhammad; Kusno Kusno (Khazanah Pendidikan, 2015)
This study aims to describe students' learning difficulties in terms of location, type and causes difficulty learning courses Linear Model. From the results of research conducted obtained: (1) the location of the learning difficulties of students in a course linear model , the indicators 2.3.1 to calculate the statistical test one way Multivariate Anova in solving problems has highest indicators of achievement that is 83,125 %, (2) The types of difficulty student learning in courses linear model, the most errors made by students in false beliefs. This suggests that students experiencing difficulty learning course materials Linear Models on the principle of ability to percentage (39.352 %). It is seen from the mistakes made by students in solving problems. Therefore it is vital that students know and master the concepts and procedures that are appropriate in solving a given problem. Key words : location , types and causes learning difficulties, diagnostic test.